2007
DOI: 10.1152/japplphysiol.01188.2005
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation attenuates corticosteroid-induced muscle wasting and impairment of exercise performance in rats

Abstract: The objective of the present study was to investigate whether creatine (Cr) could attenuate the deleterious effects of high doses of dexamethasone (Dexa) on body mass, exercise performance, and respiratory variables of rodents. Forty-four Wistar rats performed incremental maximal exercise tests. They were then assigned to four groups: G1: subcutaneous (s.c.) and intraperitoneal (i.p.) saline; G2: s.c. saline and i.p. Cr (250 mg x kg(-1) x day(-1)); G3: s.c. Dexa (7.5 mg x kg(-1) x day(-1)) and i.p. saline; G4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 43 publications
1
17
0
5
Order By: Relevance
“…This attenuation may be a direct consequence of the improvement of insulin signal transduction through the phosphatidylinositol-3-kinase/ Akt-1 pathway, IRS-1 and IRS-2 activity and GLUT-4 expression discussed earlier. (Tanner et al 2002;Luciano et al 2002) It has been suggested that DEX treatment decreases body weight in a dose-dependent manner (De Vries et al 2002;Komamura et al 2003;Ahtikoski et al 2004;Rhee et al 2004;Coderre et al 2007;Kaasik et al 2007;Menezes et al 2007;Rafacho et al 2008). In the present study, both DEX-treated groups had signiWcantly reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This attenuation may be a direct consequence of the improvement of insulin signal transduction through the phosphatidylinositol-3-kinase/ Akt-1 pathway, IRS-1 and IRS-2 activity and GLUT-4 expression discussed earlier. (Tanner et al 2002;Luciano et al 2002) It has been suggested that DEX treatment decreases body weight in a dose-dependent manner (De Vries et al 2002;Komamura et al 2003;Ahtikoski et al 2004;Rhee et al 2004;Coderre et al 2007;Kaasik et al 2007;Menezes et al 2007;Rafacho et al 2008). In the present study, both DEX-treated groups had signiWcantly reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight loss is usually followed by muscle atrophy and skeletal muscle protein loss, including collagen IV, which may aVect muscle contraction (De Vries et al 2002;Komamura et al 2003;Ahtikoski et al 2004;Lumbers et al 2005;Gilson et al 2007;Kaasik et al 2007;Menezes et al 2007). This present study demonstrated that sedentary animals had a 33.5% reduction on TA muscle weight after DEX treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dietary supplementation with creatine monohydrate has been shown to attenuate the muscle weight loss and the atrophy of gastrocnemius type IIb fibers caused by glucocorticoids (Roy et al 2002, Menezes et al 2007). Furthermore, this protective effect was associated with an attenuation of the impairment of daily spontaneous running of animals receiving glucocorticoids (Campos et al 2006).…”
Section: Creatinementioning
confidence: 99%